THE INFLUENCE OF PERSONAL SOCIAL FACTORS AND PSYCHOLOGY ON THE INTEREST IN TRANSACTIONS IN ISLAMIC BANKING - aviva aviva; sunarji harahap; jafar nasution (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Islamic banking is very much needed by the community, as well as the people of Manunggang Jae Village, Southeast Padangsidimpuan District. The problem in this study is that people prefer to make transactions in conventional banking, moneylenders and cooperatives compared to Islamic banking where the location of Islamic banking is close to Manunggang Jae Village, Southeast Padangsidimpuan District. This study aims to determine the influence of social, personal and psychological factors on interest in transactions in Islamic banking (Case Study of Manunggang Jae Village Community, Southeast Padangsidimpuan District). The discussion of this research relates to the theory put forward by Philip Kotler that the factors that influence interest are cultural, social, personal and psychological factors. In this regard, the approach taken is theories related to transactional interest, social, personal and psychological factors. And Abdul Rahman Saleh's theory says that interest is a tendency to give attention and action to activities, people or situations that are objects of interest accompanied by a sense of pleasure. This research is a descriptive quantitative research using primary data. The data collection technique used is documentation and questionnaires with a sample of 96 people with incidental sampling sampling technique using the Slovin formula, the data analysis method used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test , t test, f test and coefficient of determination test. Data processing was carried out with SPSS version 23. Based on the results of the analysis conducted by researchers, the results of the partial study (t test) showed that social (-1.661 0.195 1.661), and psychology (-1.661 1.489 1.661) had no effect on interest in transactions in Islamic banking. And personal (41, 593 1.661) has an effect on interest in transactions in Islamic banking. Judging by the social, personal, and psychological F-tests have a simultaneous effect on interest in transactions in Islamic banking with a value (892.654 2.14).